Concentration of 12 Oligosaccharides in the Milk of New Zealand Breastfeeding Women - Jia LL; Brough L; Weber JL (MDPI (Basel, Switzerland), 2023)
Human milk oligosaccharides (HMOs) are the third most abundant component in breast milk. HMOs benefit infant gut health, modulate immune responses, and promote brain development. The profile and concentration of HMOs vary considerably among breastfeeding women, and are reported to be associated with genetic, maternal, and environmental factors as well as feeding practices. One reason for the diversity in HMO concentration is the secretor gene, which determines the presence of an enzyme responsible for the synthesis of 2′-FL and LNFP-I. To date, there is no report about HMO concentration or profile in the New Zealand population. Our objective was to investigate 12 HMO concentrations in a small sample of New Zealand women. Sixty-eight breastfeeding mothers (mean age 32 years, 77% Caucasian) of singleton infants (median age [Q1, Q3] 108 [70, 166] days) were included, with 65% exclusively breastfeeding and 54% who had two or more children. Concentrations of 12 HMOs were measured by UHPLC with fluorescence detection. Overall, 68% of mothers were secretors, which was defined by the presence of 2′-FL in the milk. HMO profiles varied widely; total HMO concentration varied 4.2-fold between women; and individual HMOs varied from 4.8-fold to >100-fold. The median of total HMO concentration (Q1, Q3) of the secretors and non-secretors were 6774.9 (6395.4, 8245.6) mg/L and 7128.0 (6093.1, 7880.1) mg/L respectively. Significant differences in concentration of 2′-FL, 3-FL, A-Tet, LNFP-I, LNFP-II, LNFPV, and LNnT between secretors and non-secretors were found by Mann–Whitney tests. However, there was no significant difference in concentrations of LNFP-III, LNnFP, 3′-SL, 6′-SL, LNT, or total HMOs between the secretors and the non-secretors. HMO concentrations vary broadly between breastfeeding women. A longitudinal cohort of a larger sample size is required to fully investigate HMO profiles at different lactation stages of New Zealand women and to further explore the influence of maternal and environmental factors on HMO concentration.
Keywords: human milk oligosaccharides; breastfeeding; human lactation